The NIOSH Shield Hydraulics Inspection and Evaluation of Leg Data (Shield) Computer Program (7f22bea3-620b-4bd0-a4b9-04ee2b01eea7) - Thomas Barczak (International Conference on Ground Control in Mining, 2002)
Longwall shields provide essential ground control in Iongwall mining, yet a high percentage of shields are operating at less than peak capacity and many at well below the rated support capacity due to defective hydraulic cylinders or malfunctions in other hydraulic components. Leg pressure data are currently collected on state-of¬the-art longwall shields, but typically are not analyzed to evaluate shield performance. The National Institute for Occupational Safety and Health (NIOSH) Shield Hydraulics Inspection and Evaluation of Leg Data (SHIELD) program is a Visual Basic software system that is designed to analyze leg pressure data and identify shields that are not performing to rated specifications. The program analysis is configured to detect the following conditions: (I ) loss of leg pressure, (2) imbalance in leg pressure, (3) low set pressure, (4) low yield pressure, and (5) full extension of the bottom stage. Other performance assessment measures include the percentage of the support capacity utilized (ratio of peak load to yield load), the percent of time that a shield operates at yield load, the ratio of the set load to the yield load, and the amount of support capacity that is lost due to leaking cylinders. Historical record keeping will allow the user to select a particular shield and review the performance record as developed by the program for that shield. In addition to these performance assessment measures, the software will include an animated description of shield hydraulic systems that will describe the operation and significance of each hydraulic component and the impact of component failures on the shield's capability to provide the required roof support. A general overview of the SHIELD program is provided in the paper together with an example analysis of a 2.5-year-old Australian longwall face.